Draft Genome Sequence of Klebsiella pneumoniae Isolate PR04 - Zulkifli, M. H. (American Society for Microbiology, 2013)
Klebsiella pneumoniae PR04 was isolated from a patient hospitalized in Malaysia. The draft genome sequence of K. pneumoniae PR04 shows differences compared to the reference sequences of K. pneumoniae strains MGH 78578 and NTUH-K2044 in terms of their genomic structures.